2018
DOI: 10.13189/azb.2018.060104
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Environmental and Pathogenic Variability on Breaking of Host Rust Resistance in Wheat Cultivars under Changing Climatic Conditions

Abstract: The rust fungi especially emergence of new rust races has serious threat to global wheat production. This is mainly due to the widespread use of race-specific seedling resistance genes and evolution of new virulence races like Yr9, Yr27, and Sr31. Several quantitative disease resistance (QDR) or durable resistance genes i.e. Lr34/Yr18/Pm38/Sr57, Lr46/Yr29/Pm39/Sr58, Lr67/Yr46, Lr68 providing resistance to rust diseases at either high or low temperatures have been identified. But, changing climatic conditions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Generally, 41% grain yield increases due to disease protection by fungicide application therefore the wheat growers can greatly benefits from crop protection measures. Furthermore, fungicide application increased the thousand-grain weight, number of grains/spike and also improves the quality of straw which is widely used as animal feed in developing countries (Javaid et al, 2018). Current study also clearly demonstrated a difference in yield increase with the foliar application of appropriate fungicides.…”
Section: Discussionsupporting
confidence: 54%
“…Generally, 41% grain yield increases due to disease protection by fungicide application therefore the wheat growers can greatly benefits from crop protection measures. Furthermore, fungicide application increased the thousand-grain weight, number of grains/spike and also improves the quality of straw which is widely used as animal feed in developing countries (Javaid et al, 2018). Current study also clearly demonstrated a difference in yield increase with the foliar application of appropriate fungicides.…”
Section: Discussionsupporting
confidence: 54%
“…According to Roelf's finding, some resistance gene combinations, such as the 'Sr2 complex' for stem rust resistance [10&20], the 'Frontana complex' for leaf rust resistance [21], and the resistance of Anza and Little Joss for stripe rust [22][23], have shown long-term durability. These complexes provide the basic resistance in the emerging bread wheat germplasm at CIMMYT.…”
Section: Wheat Rustsmentioning
confidence: 99%
“…Controlling rust epidemics in the region is challenging (Ali et al, 2022b). The novel stem, leaf and yellow rusts races have been introduced to wheatgrowing areas on several continents ( Javaid et al, 2018;Ali, 2018). Screening for yellow and leaf rust is the best way to control rust diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Screening for yellow and leaf rust is the best way to control rust diseases. Comprehensive research is needed to assess yield losses and their level of rust resistance ( Javaid et al, 2018). The country lacks high-yield and rust-resistant wheat cultivars with wide adoption.…”
Section: Introductionmentioning
confidence: 99%